Pengaruh Partisipasi Organisasi Terhadap Soft Skill Mahasiswa Kampus 3 Universitas Islam Negeri Maulana Malik Ibrahim Malang - Febriana, Dista Aulia; Mustofa, Atalie Isaura Syahda (LoroNG: Media Pengkajian Sosial Budaya, 2025)
Abstract: This study aims to determine the effect of organizational participation on the development of soft skills among students at the State Islamic University (UIN) Malang Campus 3, with a focus on communication skills, emotional intelligence, critical thinking and problem-solving skills, ethics, and leadership skills. The research method used is descriptive quantitative, where data was collected through a questionnaire distributed to active students at UIN Malang Campus 3 who are involved in organizations. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) with descriptive statistical techniques to describe respondent characteristics, simple linear regression tests to determine the proportion of the influence of organizational participation on soft skills, and Spearman's correlation tests to measure the relationship between the two variables. The research findings are expected to provide empirical contributions regarding the extent to which involvement in organizations influences the development of students' soft skills, as well as serve as a reference for the university in encouraging active student participation in organizations. These findings may also serve as a basis for policymakers in higher education institutions to design more structured soft skill development programs to prepare students for global demands.